Environmental Knowledge, Environmental Value, And Environmental Behavior Of Santri At Pesantren - et. al., Edi Kurniawan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There are many studies on environmental knowledge, values, and behavior, but those that study santri at pesantren (Islamic boarding schools) are still very limited because they still focus on the general public or students in formal schools. This study aims to analyze the level of environmental knowledge, environmental value, and environmental behavior of santri at pesantren around the area of Universitas Negeri Semarang (UNNES). This research is a quantitative study using a questionnaire data collection method. The research sample consisted of 208 Islamic boarding school students (santri) of pesantren around the UNNES area who were selected by stratified random sampling technique. The data analysis used in this study consisted of percentage descriptive analysis techniques. The results showed that the santri in the UNNES area have a very high level of environmental knowledge and environmental value, and a high level of environmental behavior. These results indicate that religious-based environmental education will be more effective. For this reason, conservation education must be implemented continuously and comprehensively by involving the roles of all parties. UNNES and many pesantren in the UNNES area must strengthen their synergy to create a good-quality environmental education for UNNES students, santri, and the community around UNNES.